ESTIMATION OF ANTI-INFLAMMATORY ACTIVITY AS WELL AS APOPTOTIC ACTIVITY OF ETHANOLIC EXTRACTS OF CROCUS SATIVUS - Arirudran, B.; Priyadharshini, P.; Rao, US Mahadeva (Universal Journal of Pharmaceutical Research, 2019)
Objective: Inflammation is a body reaction which embroils cellular and biochemical responses, which is not only symptom for shared diseases but also known to be an initial phase for certain serious Alzheimer’s, cancer, heart vascular diseases. In order to overcome these drawbacks, there is an urgent need for nutraceuticals with excellent anti-inflammatory response with minimum side effects. An attempt has been made to evaluate the anti-inflammatory activity along with gene expression analysis on ethanolic extracts of Crocus sativus (CSEE). Methods: Dried stigmas of C. sativus were analyzed for anti-inflammatory activity by macrophage scavenging assay. In this study, the phagocytic activity of the extract was tested on oxidative burst reduction of macrophages. RT-PCR was performed to analyze the anti-apoptotic gene expression during cell death, as a result of the compound treatment on cancer cells. Results: The CSEE unveiled high phagocytic activity on the oxidative burst reduction, presenting intracellular killing and the enhancement of lysosomal enzyme activity, showing the active degranulation of macrophages. Conclusion: These findings suggest that C. sativus possessed excellent anti-inflammatory as well as apoptotic activities. Hence it was proposed that C. sativus could be exploited against oxidative stress, anti-inflammatory, cancer and ageing therapy to justify their use in traditional medicine as a nutraceutical. Peer Review History: Received 3 October 2018; Revised 9 November; Accepted 25 December; Available online 15 January 2019 Academic Editor: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Reviewer(s) detail: Dr. Nada Farrag , Misr International University, Egypt, Nada_Hazem87@hotmail.com Noha El Baghdady , MTI University, Cairo, Egypt, nohasalah21@yahoo.com